СЕГМЕНТИ ПУБЛІЧНОЇ ПОЛІТИКИ У СФЕРІ ОСВІТИ І НАУКИ В ДОБУ УКРАЇНСЬКОЇ НАЦІОНАЛЬНОЇ РЕВОЛЮЦІЇ (1917-1920 рр.) - Kupriychuk, Vasyl; Verbovskyi, Igor; Novitska, Inesa; Khmelivska, Svitlana (Zhytomyr Ivan Franko State University, 2023)
The article analyzes the segments of public policy in the field of education and science during the Ukrainian National Revolution. It was found out that the main principles that professed the public-state nature of education were laid down by the Ukrainian governments of 1917–1920 at the basis of national education concept. The above principles served as the methodological guidelines for the organization of the national school and have not lost their value even today. It was in the concept of building education that political, cultural and public figures gave an important role to the formation of national higher humanitarian and natural education. The first place was the creation of Ukrainian humanitarian higher educational institutions and, first of all, universities, because higher education, like no other, was the most russified and, besides, there was a low percentage of Ukrainians among the student body. The peculiarities of the public policy’s impact on the educational and scientific process at various stages of Ukrainian state formation (Ukrainian Central Rada, Hetmanate of Pavlo Skoropadskyi, Directory of the Ukrainian People's Republic and the West Ukrainian People's Republic) were considered. The transformations experience of the educational sphere at that time was summarized, and specific proposals were offered on this basis regarding the possibilities of their implementation in the practice of public administration in the field of modern Ukraine’s education and science. It is outlined that precisely in these years, compared to the pre-revolutionary period, the number of higher educational institutions increased significantly, the quality of their specialist training improved, curricula were streamlined and improved, new specializations were introduced, and Ukrainian-language teaching was introduced. Individual institutes and all universities got the right to establish graduate schools, doctorate schools and to grant research degrees to researchers. The changes in the content and social purpose of higher education and the attitude towards it are highlighted. It is emphasized that education itself began to be considered not as a separate, distant, and sometimes hostile to the interests of the people, cultural environment, but as an integral part of the nation’s cultural heritage and its gradual development.